In-situ measurements of the effect of radiation damage on the superconducting properties of coated conductors. (3rd August 2021) - Iliffe, W; Peng, N; Brittles, G; Bateman, R; Webb, R; Grovenor, C; Speller, S
Abstract: An apparatus has been built to perform irradiation and electrical testing of REBCO coated conductors (CC) held below their critical temperature ( T c ). Patterned tracks of Fujikura GdBCO CC were irradiated with 2 MeV He + ions in steps up to 4 mdpa whilst held at 40 K, and the critical current density ( J c ) determined from I–V characteristics. These ' in-situ ' samples then underwent annealing experiments at room temperature. The superconducting performance, both before and after room temperature annealing, has been compared to equivalent samples irradiated at room temperature and then cooled for testing at 40 K to understand how the damage tolerance of these materials is affected by sample temperature. Details of the apparatus and experimental results from preliminary work are presented and discussed. These preliminary results show that both T c and J c values of patterned tracks degrade with irradiation dose, with most samples showing similar behaviour. The room temperature annealing of ' in-situ ' irradiated samples resulted in a significant recovery of properties. We conclude that irradiation temperature does alter how the superconducting properties of GdBCO CC are affected by ion irradiation, and that this observation has implications for the design of high temperature superconducting magnets for future fusion reactors.